An Efficient Metal-Free Hydrophilic Carbon as a Counter Electrode for Dye-Sensitized Solar Cells - Mojgan Kouhnavard; Norasikin Ahmad Ludin; Babak Vazifehkhah Ghaffari; Kamaruzzaman Sopian; Norshazlinah Abdul Karim; Mikio Miyake (International Journal of Photoenergy)
This study presents a new cost-effective metal-free counter electrode (CE) for dye-sensitized solar cells (DSSCs). CE was prepared by doctor blading a hydrophilic carbon (HC) particle on a fluorine-doped tin oxide substrate. Thereafter, HC CE was characterized using X-ray diffraction, profilometry, four-point probe testing, and cyclic voltammetry. A 2 µm thick HC CE revealed a comparable catalytic activity to that of the Pt electrode under the same experimental conditions. DSSC based on HC CE was analyzed and showed Jsc of 6.87 mA/cm2 close to that of DSSC with Pt CE (7.0 mA/cm2). More importantly, DSSC based on HC CE yielded a power conversion efficiency (η) of 2.93% under AM 1.5 irradiation (100 mW/cm2), which was comparable to that of DSSC based on standard Pt CE. These findings suggest that HC CE could be a promising CE for low-cost DSSCs.